2017
DOI: 10.18632/oncotarget.20720
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in cyclin D1 are associated with risk of renal cell cancer in the Chinese population

Abstract: Recently, the functional polymorphisms in Cyclin D1 (CCND1) have been shown the potential influence to risk of renal cell cancer (RCC). Therefore, the present study was performed to investigate whether these polymorphisms could influence the susceptibility of RCC. Four potentially functional polymorphisms in CCND1 (rs1944129, rs7177, rs9344 and rs678653) were genotyped in this hospital-based case-control study, comprising of 1,488 RCC patients and 1,677 cancer-free controls in a Chinese population by the TaqMa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Previous research has demonstrated that ccnd1 serves an important role in promoting the development and progress of multiple types of human cancer, such as lung adenocarcinoma, glioma and renal cell cancer (46)(47)(48)(49). a previous study indicated that mir-374a inactivated the phosphoinositide 3-kinase (Pi3K)/aKT signaling axis through inhibiting ccnd1 and suppressing the progression of colon cancer (49).…”
Section: Ccnd1 Is Required For the Proliferation And Apoptosis Of Ht-mentioning
confidence: 99%
“…Previous research has demonstrated that ccnd1 serves an important role in promoting the development and progress of multiple types of human cancer, such as lung adenocarcinoma, glioma and renal cell cancer (46)(47)(48)(49). a previous study indicated that mir-374a inactivated the phosphoinositide 3-kinase (Pi3K)/aKT signaling axis through inhibiting ccnd1 and suppressing the progression of colon cancer (49).…”
Section: Ccnd1 Is Required For the Proliferation And Apoptosis Of Ht-mentioning
confidence: 99%
“…cyclin d1 (ccnd1), a member of the highly conserved cyclin family, can function as a modulator of cyclin-dependent kinase (cdK)4 or cdK6, and has an important role in adjusting the progression of the cell cycle (32,33). Previous studies revealed that ccnd1 has a crucial role in promoting proliferation, migration and tumor metastasis (34,35) in cancers such as lung cancer (33), gastric cancer (36) and renal cell cancer (37). ccnd1 has been reported to exhibit a high expression in Tc tissues and to be associated with invasive behavior (38).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin D1 gene, second important molecule of cell cycle pathway has also been found mutated in almost every human cancer by altering the normal cell cycle pathway. CCND1 gene polymorphisms have been found in several cancers [38][39][40][41][42][43][44][45][46][47] including gliomas also [48]. However, till now no study has been published with respect to brain tumor and different subtypes of brain tumor such as glioma, meningioma and pituitary adenoma.…”
Section: Discussionmentioning
confidence: 99%